THE NEW BANK OF THE SOUTH SHATTERS NEOLIBERAL ECONOMICS - Engler, Mark (La Sociología en sus Escenarios, 2012)
Resumen. Un grupo de líderes latinoamericanos han inaugurado el Banco del Sur. Este banco apoyará el desarrollo regional compitiendo con el Banco Interamericano de Desarrollo (BID) y el Banco Mundial. Abstract. A group of Latin American leaders has inaugurated the Bank of the South. This bank will support the regional development competing with the International Monetary Fund and the World Bank.